1 | | Given two relations `a ? b` and `c ! d`, first I check whether `?` and `!` are the same relation. If so, I have a couple of cases. One, if `?` and `!` are both `==` or are both `!=`, then I check whether `a == c` and `b == d`, or `a == d` and `b == c`. Two, if `?` and `!` are some other relation than `==` or `!=`, then I only allow the case `a == c` and `b == d`. |

| 1 | Given two relational expressions `a ? b` and `c ! d`, first I check whether `?` and `!` are the same relation. If so, I have a couple of cases. One, if `?` and `!` are both `==` or are both `!=`, then I check whether `a == c` and `b == d`, or `a == d` and `b == c`. Two, if `?` and `!` are some other relation than `==` or `!=`, then I only allow the case `a == c` and `b == d`. |